Development of Embedded System Learning Module Using Project-based Learning Method for Industrial Electronics Department - Pratama, Diaz Octa; Handayani, Anik Nur (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
The problem faced in the Industrial Electronics Department of Vocational High School (Sekolah Menengah Kejuruan/SMK) PGRI 3 Malang is the unavailability of systematic teaching materials in the learning process of embedded systems. The module is one of the teaching materials used to improve students’ quality and produce independent and creative students. This research aims to develop Embedded System Learning Module using Project-based Learning method to overcome the urgent need for teaching materials. The research methodology used is R&D with the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation. The steps of developing this module include: 1) Analysis: identifying the needs of teaching materials; 2) Design: designing the elements needed in the learning module; 3) Development: making and validating the module by material and media experts; 4) Implementation: Small and large group trials in class XI of the Industrial Electronics department of SMK PGRI 3 Malang; 5) Evaluate: module feasibility analysis. Data collection in this study used interviews, observations, and questionnaire instruments. Product validation results were obtained from media experts, with a percentage of 87.5% (very valid), and material experts, with a rate of 95% (very valid). After the developed product received feasible criteria from the experts, a small group trial (10 students) and a large group trial (24 students) were conducted. The results of the small group trial were 85.7% (very valid), and the results of the large group trial were 87.8% (very valid). Therefore, this module is feasible for teaching material in learning embedded systems.